Analisis Kebijakan Peraturan Daerah Kabupaten Tebo Tentang Pelayanan Pendidikan - Bashori, Bashori; Nurzakiah, Nurzakiah (Itqan: Jurnal Ilmu-ilmu Kependidikan, 2021)
Quality education services can develop the potential of students to the fullest. The purpose of this study was to analyze the regional regulations of Tebo Regency. This study uses a qualitative method with a literature study approach. The data sources in this study used primary data sources in the form of policy Number 1 of 2013 concerning Education Services and secondary data sources from various sources that support both journals and books related to policies. The data analysis technique used is in the form of content analysis. The results of this study indicate that the Education Service Policy has been regulated in the regional regulation policy of Tebo Regency Number 1 of 2013 concerning Education Services, as has been stipulated in the policy of the regulation regarding educational services, namely through: 1) 12 -Year Compulsory Education Pilot Program, 2) Children's Education Early Age, 3) Educators and Education Personnel